2020
DOI: 10.1002/mds.28210
|View full text |Cite
|
Sign up to set email alerts
|

Residual Injurious Symptoms and Its Association With Neurodegenerative Outcomes in Idiopathic Rapid Eye Movement Sleep Behavior Disorder: A Retrospective, Longitudinal Follow‐up Study

Abstract: A BS TRACT: Background: The risk of neurodegenerative disorders in idiopathic rapid eye movement sleep behavior disorder (iRBD) patients with residual injurious symptoms (RIS) after symptomatic treatment with clonazepam and/or melatonin is unclear. Objective: The objective of this study was to determine the rate and correlates of RIS and its association with the risk of neurodegenerative diseases in patients with iRBD. Methods: This was a retrospective cohort study. RIS was defined by the RBD Questionnaire-Hon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…The major limitation of this study was the diagnostic issue for the piRBD group. Although RBDQ-HK has high internal consistency and test–retest reliability to screen piRBDs in China (sensitivity = 82.2%, specificity = 86.9%, positive predictive value = 86.3%, and negative predictive value = 83.0% 50 , 51 ), considering the absence of comprehensive neuropsychological tests and the substantial difference in MoCA scores, especially in patients with piRBD, early-stage dementia with Lewy bodies without parkinsonism may be included in the piRBD group. In the future, we plan to follow-up on these piRBDs in a longitudinal cohort study to further corroborate the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…The major limitation of this study was the diagnostic issue for the piRBD group. Although RBDQ-HK has high internal consistency and test–retest reliability to screen piRBDs in China (sensitivity = 82.2%, specificity = 86.9%, positive predictive value = 86.3%, and negative predictive value = 83.0% 50 , 51 ), considering the absence of comprehensive neuropsychological tests and the substantial difference in MoCA scores, especially in patients with piRBD, early-stage dementia with Lewy bodies without parkinsonism may be included in the piRBD group. In the future, we plan to follow-up on these piRBDs in a longitudinal cohort study to further corroborate the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our previous longitudinal study found that clonazepam did not influence the REM sleep EMG level at nearly 2 and a half years of follow-up. 43,50 In addition, the observation of REM sleep behavioral event was not rater-blind, and a potential bias might exist that technicians might not have paid much attention to REM sleep behavioral events among controls. It should be noted that there was a high variability of REM sleep behavioral events between 2 nights video-PSG recording.…”
Section: Discussionmentioning
confidence: 99%
“…22 DEBs were evaluated by the Diagnostic Interview for Sleep Patterns and Sleep Disorders and supplemented by the RBD questionnaire-Hong Kong (factor 2 score ≥8). 23,24 Lifetime psychiatric disorders were assessed via a structured interview based on the DSM-IV and further supplemented by clinical records. 25,26 Current medications usage, including antidepressants, antipsychotics, and antiepileptics, were collected during the interview and supplemented by clinical records.…”
Section: Methodsmentioning
confidence: 99%
“…DEBs were evaluated by the Diagnostic Interview for Sleep Patterns and Sleep Disorders and supplemented by the RBD questionnaire‐Hong Kong (factor 2 score ≥8) 23,24 . Lifetime psychiatric disorders were assessed via a structured interview based on the DSM‐IV and further supplemented by clinical records 25,26 .…”
Section: Methodsmentioning
confidence: 99%